P107 RENAL DENERVATION IMPROVES 24-HOUR CENTRAL AND PERIPHERAL BLOOD PRESSURES, ARTERIAL STIFFNESS AND PERIPHERAL RESISTANCE - Christian Ott; Klaas Franzen; Tobias Graf; Joachim Weil; Roland Schmieder; Michael Reppel; Kai Mortensen (Artery Research, 2018)
Background: Ambulatory Blood Pressure (BP) as well as central BP are better predictors for overall cardiovascular risk and mortality than brachial BP. Renal Denervation (RDN) has been shown to reduce office brachial and central BP as well as ambulatory brachial BP, but data on central ambulatory BP are limited. We therefore aimed to study the effect of RDN also on central hemodynamics assessed under ambulatory conditions. Methods: In total 94 patients with treatment resistant hypertension (TRH) (office BP ≥140/90 mmHg, and diagnosis confirmed by mean daytime brachial ambulatory BP ≥135/85 mmHg) who underwent RDN (using Medtronic Symplicity™ RDN radiofrequency ablation catheter system) were included. Ambulatory BP, including central pressures, hemodynamics and arterial stiffness, were measured at baseline and 3, 6, 12 months after RDN by an oscillometric device (MobiloGraph™, I.E.M., Germany). Results: Office BP was significantly reduced at all time points (p for all <0.001). At 3, 6 and 12 months follow-up, brachial ambulatory BP was reduced by 6 ± 13/4 ± 7 mmHg, 8 ± 15/4 ± 10 mmHg, 9 ± 16/4 ± 9 mmHg, respectively (p for all <0.001). Consistently, central ambulatory BP was reduced by 6 ± 12/3 ± 8 mmHg, 7 ± 15/4 ± 9 mmHg, 9 ± 15/5 ± 9 mmHg, respectively (p for all <0.001). In addition, ambulatory assessed averaged daytime pulse wave velocity improved after RDN (p < 0.05). Total vascular resistance decreased by 4.0 %/5.5 %/6.7 % (p for all <0.01). In contrast, cardiac output was not altered during follow-up. Conclusion: In patients with TRH, RDN improves brachial and central ambulatory BP, arterial stiffness and total vascular resistance, indicating an improvement of cardiovascular outcome.